Pathogenicity and virulence of human adenovirus F41: Possible links to severe hepatitis in children - Roger J. Grand (Virulence)
Over 100 human adenoviruses (HAdVs) have been isolated and allocated to seven species, A-G. Species F comprises two members-HAdV-F40 and HAdV-F41. As their primary site of infection is the gastrointestinal tract they have been termed, with species A, enteric adenoviruses. HAdV-F40 and HAdV-F41 are a common cause of gastroenteritis and diarrhoea in children. Partly because of difficulties in propagating the viruses in the laboratory, due to their restrictions on growth in many cell lines, our knowledge of the properties of individual viral proteins is limited. However, the structure of HAdV-F41 has recently been determined by cryo-electron microscopy. The overall structure is similar to those of HAdV-C5 and HAdV-D26 although with some differences. The sequence and arrangement of the hexon hypervariable region 1 (HVR1) and the arrangement of the C-terminal region of protein IX differ. Variations in the penton base and hexon HVR1 may play a role in facilitating infection of intestinal cells by HAdV-F41. A unique feature of HAdV-F40 and F41, among human adenoviruses, is the presence and expression of two fibre genes, giving long and short fibre proteins. This may also contribute to the tropism of these viruses. HAdV-F41 has been linked to a recent outbreak of severe acute hepatitis “of unknown origin” in young children. Further investigation has shown a very high prevalence of adeno-associated virus-2 in the liver and/or plasma of some cohorts of patients. These observations have proved controversial as HAdV-F41 had not been reported to infect the liver and AAV-2 has generally been considered harmless.